Approximation of phenol concentration using novel hybrid computational intelligence methods - Pławiak, Paweł; Tadeusiewicz, Ryszard (1947- ) (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents two innovative evolutionary-neural systems based on feed-forward and recurrent neural networks used for quantitative analysis. These systems have been applied for approximation of phenol concentration. Their performance was compared against the conventional methods of artificial intelligence (artificial neural networks, fuzzy logic and genetic algorithms).
Keywords: soft computing; neural networks; genetic algorithms; fuzzy systems; evolutionary-neural systems; pattern recognition; chemometrics